Learning achievement of the students after completion of grade five from BRAC schools - Hossain, Md. Altaf; Akter, Shaheen; Kalam, Md. Abul (BRAC Research and Evaluation Division (RED), 2020)
The Non-Formal Primary Education (NFPE) programme of BRAC introduced class four and five to its curriculum to mesh with the formal primary education. BRAC launched this primary education programme in its 1000 schools throughout the country on a pilot basis and provided one-year additional schooling to cover classes four and five. At the end of the first cycle, this study is initiated to evaluate the performance of the learners to measure the overall performance of the programme.